Superiority of integrated cervicothoracic immobilization in the setup of supraclavicular in lung cancer patients treated with supraclavicular station irradiaotionherapy - Wan, Bao; Luo, Shihong; Feng, Xin; Qin, Wenhua; Sun, Haifan; Hou, Lu; Zhang, Kun; Wu, Shiyu; Zhou, Zongmei; Feng, Qinfu; Chen, Dongfu; Xiao, Zefen; et al. (Frontiers in Oncology)
Objective: To investigate the superiority of the integrated cervicothoracic immobilization devices (ICTID) on the mobility of the supraclavicular station in lung cancer patients requiring both primary lung lesion and positive supraclavicular lymph nodes irradiation. Methods: One hundred patients with lung cancer were prospectively enrolled in the study. The following four different fixation methods are used for CT simulation positioning: thoracoabdominal flat immobilization device fixation with arms lifting (TAFID group), head-neck-shoulder immobilization device fixation with arms on the body sides (HNSID group), ICTID fixation with arms on the body sides (ICTID arms-down group), and n ICTID fixation with arms lifting (ICTID arms-up group). Cone-beam computed tomography (CBCT) images are taken daily or weekly before treatment，to assess anatomical changes during the radiotherapy course. Results: The translation errors in X (left-right direction), Y (head-foot direction), and Z (abdomen-back direction) directions of the ICTID arms-up, TAFID, ICTID arms-down and HNSID groups were (0.15 ± 0.18) cm, (0.15 ± 0.16) cm, (0.16 ± 0.16) cm, and (0.15 ± 0.20) cm; (0.15 ± 0.15) cm, (0.21 ± 0.25) cm, (0.28 ± 0.23) cm, and (0.27 ± 0.21) cm; (0.13 ± 0.14) cm, (0.15 ± 0.14) cm, (0.17 ± 0.13) cm, and (0.16 ± 0.14) cm, respectively. Among them, the ICTID arms-up group had the minimal setup errors in X direction than those in ICTID arms-down (p=0.001) and HNSID groups (p=0.001), and in Y direction than those in TAFID (p<0.001), and in Z direction than those in ICTID arms-down (p<0.001) and TAFID groups (p=0.034). For the rotational errors of the four groups in the directions of sagittal plane, transverse plane, and coronal plane, the ICTID arms-up group had the smallest setup errors in the sagittal plane than that of TAFID groups and similar rotation setup errors with those of the other three groups. Conclusion: For patients requiring radiation of primary lung lesion and positive supraclavicular lymph nodes, an integrated frame fixation device is preferred the ICTID arms-up methods provide the smallest set up error and satisfied repeatability of body position, compared with TAFID and HNSID.